Robot-Assisted Electrode Array Insertion Becomes Available in Pediatric Cochlear Implant Recipients: First Report and an Intra-Individual Study - Jia, Huan; Pan, Jinxi; Gu, Wenxi; Tan, Haoyue; Chen, Ying; Zhang, Zhihua; Jiang, Mengda; Li, Yun; Sterkers, Olivier; Wu, Hao (Frontiers in Surgery, 2021)
Background: As an advanced surgical technique to reduce trauma to the inner ear, robot-assisted electrode array (EA) insertion has been applied in adult cochlear implantation (CI) and was approved as a safe surgical procedure that could result in better outcomes. As the mastoid and temporal bones are generally smaller in children, which would increase the difficulty for robot-assisted manipulation, the clinical application of these systems for CI in children has not been reported. Given that the pediatric candidate is the main population, we aim to investigate the safety and reliability of robot-assisted techniques in pediatric cochlear implantation. Methods: Retrospective cohort study at a referral center in Shanghai including all patients of simultaneous bilateral CI with robotic assistance on one side (RobOtol® system, Collin ORL, Bagneux, France), and manual insertion on the other (same brand of EA and CI in both side), from December 2019 to June 2020. The surgical outcomes, radiological measurements (EA positioning, EA insertion depth, mastoidectomy size), and audiological outcomes (Behavior pure-tone audiometry) were evaluated. Results: Five infants (17.8±13.5 months, ranging from 10 to 42 months) and an adult (39 years old) were enrolled in this study. Both perimodiolar and lateral wall EAs were included. The robot-assisted EA insertion was successfully performed in all cases, although the surgical zone in infants was about half the size in adults, and no difference was observed in mastoidectomy size between robot-assisted and manual insertion sides (p=0.219). The insertion depths of EA with two techniques were similar (P=0.583). The robot-assisted technique showed no scalar deviation, but scalar deviation occurred for one manually inserted pre-curved EA (16%). Early auditory performance was similar to both techniques. Conclusion: Robot-assisted technique for EA insertion is approved to be used safely and reliably in children, which is possible and potential for better scalar positioning and might improve long-term auditory outcome. Standard mastoidectomy size was enough for robot-assisted technique. This first study marks the arrival of the era of robotic CI for all ages.